Bioinspired Chemical Sensors and Micro-Nano Devices - Ping Wang; Chunsheng Wu; Liujing Zhuang (Chemosensors, 2022)
Biological smell and taste systems can recognize the specific chemical signals presented by various odorants and taste substances with extremely high performance, which cannot be achieved by current artificial devices [...]